Non-motor symptoms burden, mood, and gait problems are the most significant factors contributing to a poor quality of life in non-demented Parkinson's disease patients: Results from the COPPADIS Study Cohort. (September 2019) - ; Adarmes, A.D.; Almeria, M.; Alonso Losada, G.; Alonso Cánovas, A.; Alonso-Frech, F.; Arribas, S.; Ascunde Vidondo, A.; Aquilar, M.; Ávila, M.A.; Bernardo Lambrich, N.; Bejr-Kasem, H.; et al.
Abstract: Objective: To identify factors related to a poor health-related and global quality of life (QoL) in a cohort of non-demented Parkinson's disease (PD) patients and compare to a control group. Methods: The data correspond to the baseline evaluation of the COPPADIS-2015 Study, an observational, 5-year follow-up, multicenter, evaluation study. Three instruments were used to assess QoL: (1) the 39-item Parkinson's disease Questionnaire (PDQ-39), (2) a subjective rating of global QoL (PQ-10), and (3) the EUROHIS-QOL 8-item index (EUROHIS-QOL8). Multiple linear regression methods were used to evaluate the direct impact of different variables on these QoL measures. Results: QoL was worse in PD patients (n = 692; 62.6 ± 8.9 years old, 60.3% males) than controls (n = 206; 61 ± 8.3 years old, 49.5% males): PDQ-39, 17.1 ± 13.5 vs 4.4 ± 6.3 (p < 0.0001); PQ-10, 7.3 ± 1.6 vs 8.1 ± 1.2 (p < 0.0001); EUROHIS-QOL8, 3.8 ± 0.6 vs 4.2 ± 0.5 (p < 0.0001). A high correlation was observed between PDQ-39 and Non-Motor Symptoms Scale (NMSS) (r = 0.72; p < 0.0001), and PDQ-39 and Beck Depression Inventory-II (BDI-II) (r = 0.65; p < 0.0001). For health-related QoL (PDQ-39), non-motor symptoms burden (NMSS), mood (BDI-II), and gait problems (Freezing Of Gait Questionnaire [FOGQ]) provided the highest contribution to the model (β = 0.32, 0.28, and 0.27, respectively; p < 0.0001); whereas mood and gait problems contributed the most to global QoL (PQ-10, β = -0.46 and −0.21, respectively; EUROHIS-QOL8, β = -0.44 and −0.23, respectively). Conclusions: QoL is worse in PD patients than in controls. Mood, non-motor symptoms burden, and gait problems seem to be the most relevant factors affecting health-related and global perceived QoL in non-demented PD patients. Highlights: Non-motor symptoms (NMS) are frequent in Parkinson's disease (PD) patients during the first steps of the disease. Health-related and global perceived quality of life (QoL) are worse in PD patients than controls. Strong correlation was observed between PQ-10 and EUROHIS-QOL8, both scales to provide global QoL. NMS burden, mood, and gait problems are the most significant factors contributing to a worse QoL. In practice, it is necessary to ask about NMS, mood, and gait problems in PD patients during their first years of evolution.